Umbilical Cord-Derived Mesenchymal Stem Cells Relieve Hindlimb Ischemia through Enhancing Angiogenesis in Tree Shrews - Cunping Yin; Yuan Liang; Jian Zhang; Guangping Ruan; Zian Li; Rongqing Pang; Xinghua Pan (Stem Cells International)
Hindlimb ischemia is still a clinical problem with high morbidity and mortality. Patients suffer from consequent rest pain, ulcers, cool limbs, and even amputation. Angiogenesis is a promising target for the treatment of ischemic limbs, providing extra blood for the ischemic region. In the present study, we investigated the role of umbilical cord-derived mesenchymal stem cells (UC-MSCs) in regulating angiogenesis and relieving hindlimb ischemia. UC-MSCs were isolated from the umbilical cord of tree shrews. Angiography results showed that UC-MSCs injection significantly promoted angiogenesis in tree shrews. Moreover, the ankle brachial index, transcutaneous oxygen pressure, blood perfusion, and capillary/muscle fiber ratio were all markedly increased by the application of UC-MSCs. In addition, the conditioned culture of human umbilical vein endothelial cells using medium collected from UC-MSCs showed higher expression of angiogenic markers and improved migration ability. In short, the isolated UC-MSCs notably contributed to restoring blood supply and alleviating the symptoms of limb ischemia through enhancing angiogenesis.